2003
DOI: 10.1021/bi0353629
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of Thioredoxin Reductase from Plasmodium falciparum by Mannich Bases. Implication for Cytotoxicity

Abstract: Thioredoxin reductase (TrxR) is the homodimeric flavoenzyme that catalyzes reduction of thioredoxin disulfide (Trx). For Plasmodium falciparum, a causative agent of tropical malaria, TrxR is an essential protein which has been validated as a drug target. The high-throughput screening of 350000 compounds has identified Mannich bases as a new class of TrxR mechanism-based inhibitors. During catalysis, TrxR conducts reducing equivalents from the NADPH-reduced flavin to Trx via the two redox-active cysteine pairs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 38 publications
6
71
0
2
Order By: Relevance
“…Sortase Converts AAEKs to Reactive Olefin IntermediatesWe hypothesized that the ␤-carbon of AAEK1 or AAEK2 may be linked via Michael-type addition by the sortase thiol to an olefin intermediate generated by amine elimination (42,43). If so, addition of exogenous thiol would be expected to "capture" the olefin intermediate, thereby preventing the modification of (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sortase Converts AAEKs to Reactive Olefin IntermediatesWe hypothesized that the ␤-carbon of AAEK1 or AAEK2 may be linked via Michael-type addition by the sortase thiol to an olefin intermediate generated by amine elimination (42,43). If so, addition of exogenous thiol would be expected to "capture" the olefin intermediate, thereby preventing the modification of (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These activities have been attributed to the liberation of ␣,␤-unsaturated ketones by internal elimination of the amino group. Although this reaction proceeds very slowly under physiological pH in water it has been reported that protein surfaces are able to catalyze this reaction very efficiently (49). Such soft electrophiles, termed Michael addition acceptors, can alkylate protein nucleophiles such as cysteine, tyrosine, and serine.…”
Section: Resultsmentioning
confidence: 99%
“…After various intervals (0.5-10 min) of incubation, the enzymatic activity was measured by adding 1 mM GSSG to the mixture and compared with that of an untreated control. Based on this second approach a second-order rate constant of the reaction between enzyme and inhibitor was determined from the equation (22).…”
Section: Methodsmentioning
confidence: 99%